Determinants of employees' work motivation among business process outsourcing (BPO) companies in Ilocos Norte, Philippines - Factores, Mikee Charlemagne P. (Ilocos Norte : [s.n.], 2019)
The study determined the level of employees work motivation and the determinants of employees work motivation among the business process outsourcing companies in Ilocos Norte Philippines. the study followed the descriptive method of research using a survey questionnaire to gather data from 155 employees from the business process outsourcing companies in Ilocos Norte they were chosen purposively, they are working in the companies for at least six months, they belong to the rank and file and were willing to participate in the study.The data gathered were analyzed and interpreted using frequency,percentage,weighted mean,Pearson r of correlation and coefficient of determination.
Bibliography: pages 79-84.
CHED-La Union
Keywords: Employee motivation; Employee attitude